A Review of Two Population Growth Models and an Analysis of Factors Affecting the Chinese Population Growth - Wei, Huabin; Jiang, Yanqing; Zhang, Yuxing (Asian Journal of Economic Modelling, 2015)
This paper reviews two population growth models and tries to find out a proper way to explain and predict population growth. It shows that the exponential growth model and logistic growth model should not be used to predict population growth. The paper highlights the difference between human population growth and biological population growth and analyzes factors affecting population growth based on data available. Evidence from time series analysis indicates that, two factors, the degree of urbanization and the sex ratio, have significant influences on population growth in China.